Boron-silver co-doped copper oxide composite material, preparation method thereof and application of boron-silver co-doped copper oxide composite material in electrocatalytic carbon dioxide reduction
By using boron silver co-doped copper oxide composite materials in electrocatalytic CO2 reduction, the problems of low selectivity and low current density in electrocatalytic CO2 reduction are solved, and efficient C2 gas product generation and Faraday efficiency improvement are achieved.
Patent Information
- Application Number
- CN202411818022.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-11
AI Technical Summary
The existing Cu-based nanomaterials have problems such as low selectivity, unclear reaction mechanism, insufficient catalyst stability and low current density in electrocatalytic CO2 reduction.
Using boron silver co-doped copper oxide composite material, a composite material with regular and high activity is formed by growing a three-dimensional porous copper film on a carbon paper support, and then doping boron nanosheets and silver nanoparticles on the copper hydroxide nanowire structure template.
The selectivity and Faraday efficiency of C2 gas products that have electrocatalyzed CO2 reduction have been improved, specifically, the products of C2H4 and C2H6 have reached the highest, and the Faraday efficiency of the total C2 gas products is about 51%.
Smart Images

Figure CN119593010A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to a boron-silver co-doped copper oxide composite material, a preparation method thereof, and application thereof in electrocatalytic carbon dioxide reduction. Background Art
[0002] With the rapid development of the global economy and the excessive consumption of fossil fuels, energy crisis and global warming are becoming increasingly serious. To achieve carbon neutrality and control the rise in temperature has become a global consensus topic. 2 Resource recovery technology has become a research hotspot, among which electrocatalytic CO 2 Reduction reaction (CO 2 RR) technology is considered to be a promising CO2 reduction technology due to its advantages such as simple equipment, high environmental compatibility, mild reaction conditions and ability to be combined with renewable energy such as solar or wind energy. 2 Resource recycling strategy. In electrochemical reduction of CO 2 In the research, Cu-based nanomaterials are one of the most studied cathode materials, but there are still problems such as low selectivity of high-value products, unclear internal reaction mechanism, insufficient research on catalyst stability, and low current density. Doping, alloying or molecular modification introduces one or more elements and adjusts the main products by changing the ratio of elements, which provides a feasible method for changing the structure of copper-based catalysts. The electrocatalytic performance of its materials can be improved. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a boron-silver co-doped copper oxide composite material, a preparation method thereof, and an application thereof in electrocatalytic carbon dioxide reduction.
[0004] The first object of the present invention is to provide a method for preparing a boron-silver co-doped copper oxide composite material, comprising the following steps:
[0005] providing a carbon paper;
[0006] Using copper salt solution as electrolyte, the substrate material of three-dimensional porous copper film is grown on the surface of carbon paper by chronopotentiometry;
[0007] The obtained base material is added into a mixed solution of an oxidant and an alkali, and allowed to stand for reaction to obtain a template with copper hydroxide nanowires loaded on the surface;
[0008] Dropping a boron source solution onto the surface of the copper hydroxide nanowires in the obtained template, drying and then annealing at high temperature to obtain a copper oxide composite material doped with boron nanosheets;
[0009] The copper oxide composite material doped with boron nanosheets is reacted with a silver salt solution to obtain a boron-silver co-doped copper oxide composite material.
[0010] In the present invention, carbon paper has no selectivity for carbon dioxide reduction and will not affect the catalyst performance, so carbon paper is selected. Other carriers such as metal substrates may affect the selectivity of the reduction product. 2 The formation process of the nanowire structure is actually an oxidative dehydration process. Under the action of high concentration of alkali and oxidant ammonium persulfate, it is oxidized to form Cu 2+ According to coordination theory, copper ions and ammonia ions form a nano-ligand structure. - The chemical stability is stronger than NH 4 + , which will promote OH - Package Cu 2+ Form a square plane coordinated structure.
[0011] In some embodiments of the present invention, the copper salt in the copper salt solution is selected from copper sulfate;
[0012] The concentration of the copper salt solution is 55-65 g / L, illustratively, it can be 55 g / L, 56 g / L, 57 g / L, 58 g / L, 59 g / L, 60 g / L, 61 g / L, 62 g / L, 63 g / L, 64 g / L, 65 g / L, etc., or any interval value between any two values;
[0013] The copper salt solution also includes an acid;
[0014] The acid is selected from one or more of sulfuric acid, hydrochloric acid, and phosphoric acid;
[0015] The concentration of the acid is 80-100 g / L, and illustratively, can be 80 g / L, 90 g / L, 100 g / L, etc., or any interval value between any two values.
[0016] In some embodiments of the present invention, the conditions of chronopotentiometry are: current of 2.5-3.5 A, and deposition time of 15-25 s.
[0017] In some embodiments of the present invention, the concentration of the oxidant in the mixed solution is 0.045-0.055 mol / L; the concentration of the base in the mixed solution is 0.11-0.12 mol / L;
[0018] The oxidant is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide and potassium permanganate;
[0019] The base is selected from sodium hydroxide and / or potassium hydroxide.
[0020] In some embodiments of the present invention, the boron source in the boron source solution is selected from boric acid and / or boron oxide.
[0021] In some embodiments of the present invention, the concentration of the boron source solution is 9-11 mg / mL.
[0022] In some embodiments of the present invention, the conditions of high temperature annealing treatment are as follows: the high temperature is 450-550° C., and the annealing time is 110-120 min.
[0023] The second object of the present invention is to provide a boron-silver co-doped copper oxide composite material, characterized in that it is obtained by the preparation method; the boron-silver co-doped copper oxide composite material uses carbon paper as a carrier, and the carrier is loaded with copper oxide and a small amount of CuO x , the copper oxide and CuO x Doped with boron nanosheets and silver nanoparticles, the CuO x Represents the oxide of low-valent copper.
[0024] The doping amount of the boron nanosheets is 1.00-1.40 wt %; and the loading amount of the silver nanoparticles is 30-41 wt %.
[0025] The third object of the present invention is to provide an application of the boron-silver co-doped copper oxide composite material in electrocatalytic carbon dioxide reduction.
[0026] Furthermore, the boron-silver co-doped copper oxide composite material is electrocatalytically reduced to carbon dioxide. 2 Application of gas products.
[0027] Furthermore, the C 2 The gaseous products mainly include C 2 H 4 With C 2 H 6 , and a small amount of ethanol and acetic acid; C 1 The only product is carbon monoxide.
[0028] The boron-silver co-doped copper oxide composite material prepared by the present invention is applied to electrocatalytic carbon dioxide reduction. At a constant voltage of -1V (V vs. RHE), the material has an expected target product C 2 H 4 With C 2 H 6 Reaching the highest, its total C 2 The Faradaic efficiency (FE) of the gas product is about 51%.
[0029] The above technical solution of the present invention has the following advantages compared with the prior art:
[0030] 1. The porous fluffy copper hydroxide nanowire structure prepared by a simple redox method is used as a template. The copper hydroxide nanowire structure template is then annealed with a boric acid solution at high temperature and then reacted with silver nitrate to undergo an galvanic replacement reaction, thereby preparing a regular, surface-active boron-silver co-doped copper oxide composite material.
[0031] 2. The boron-silver co-doped copper oxide composite material prepared by the present invention utilizes the good electrocatalytic performance of Cu metal to produce CO 2 Based on the performance, the co-doping of boron and silver elements was further introduced. The doping of B element can further stabilize the copper-based catalyst in CO 2 Active Cu formed on the surface during electrochemical reduction δ+ (0≤δ≤1), which is helpful for electrochemical CO 2 Reduction reaction (CO 2 At the same time, the CO bonding strength on the CuO / Ag interface is stronger, there are more active sites, and the charge transfer speed is faster. 2 In the RR process, CC further couples to form C2 product. This material is easy to synthesize and has low cost. It is mainly prepared by redox method to prepare boron-silver co-doped copper oxide composite material with controllable morphology and size. This composite material can be used for electroreduction of CO 2 field. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0033] Figure 1 This is a SEM image of the three-dimensional porous copper structure template prepared in this example.
[0034] Figure 2 This is the SEM image of the prepared copper hydroxide nanowire structure template.
[0035] Figure 3 This is the SEM image of the prepared boron-silver co-doped copper oxide composite material. From the image, it can be seen that boron nanosheets and silver nanoparticles are doped on the copper oxide nanowires.
[0036] Figure 4 This is the Faraday efficiency (FE) diagram of electrochemical reduction of low-concentration boron-silver co-doped copper oxide composite material.
[0037] Figure 5 This is the Faraday efficiency (FE) diagram of electrochemical reduction of high concentration boron-silver co-doped copper oxide composite material.
[0038] Figure 6This is the Faraday efficiency (FE) diagram of electrochemical reduction of silver-doped copper oxide composite materials.
[0039] Figure 7 This is the Faraday efficiency (FE) diagram of electrochemical reduction of boron-doped copper oxide composite materials.
[0040] Figure 8 This is the Faraday efficiency (FE) diagram of the electrochemical reduction of copper oxide materials.
[0041] Fig. 9 This is the Faraday efficiency (FE) diagram of electrochemical reduction of boron-silver co-doped copper oxide composite material.
[0042] Fig.10 This is the linear scan (LSV) diagram of electrochemical reduction of carbon dioxide by boron-silver co-doped copper oxide composite material.
[0043] Fig.11 This is the EDS energy spectrum elemental analysis diagram of the prepared boron-silver co-doped copper oxide composite material. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0045] Example 1
[0046] This embodiment provides a method for preparing a boron-silver co-doped copper oxide composite material, comprising the following steps:
[0047] (1) Clean 0.5 mm thick carbon paper with acetone, ethanol and deionized water for 10 min respectively, and finally dry it in a constant temperature air drying oven for later use;
[0048] (2) Prepare 60g / L Cu 2 SO 4 ·5H 2 O, 90g / L H 2 SO 4 The mixed solution was used as the electrolyte, the carbon paper in step (1) was used as the working electrode, and the copper sheet was used as the counter electrode. The chronopotentiometry was used in a two-electrode system. A current of 3A was applied and deposited for 20 seconds. A three-dimensional porous copper film was grown on the surface of the carbon paper. The structure of the obtained base material was characterized. The experimental results are shown in Figure 1 .Depend on Figure 1 It can be seen that a porous and fluffy copper film structure is generated on the base material. This fluffy and porous structure increases the contact area of the reaction.
[0049] (3) Prepare a mixed solution of ammonium persulfate and sodium hydroxide, wherein the concentration of ammonium persulfate is 0.05 mol / L and the concentration of sodium hydroxide is 0.12 mol / L; add the substrate material obtained in step (2) to 5 ml of the mixed solution of ammonium persulfate and sodium hydroxide; refrigerate at 5° C. for 20 min; take out and rinse with deionized water, dry naturally for one day, and obtain a template with copper hydroxide nanowires loaded on the surface. The obtained material is structurally characterized. The results are shown in FIG. Figure 2 .from Figure 2 It can be seen that a large number of copper hydroxide nanowire structures are grown on the porous copper film.
[0050] (4) Prepare a 10 mg / mL boric acid aqueous solution, drop the prepared solution onto the surface of the copper hydroxide nanowire template prepared in step (3), and dry at 60° C. Then, place the dried sample in a muffle furnace and anneal at 500° C. for 120 minutes.
[0051] (5) After taking out the material prepared in step (4), put it into a 5mmol / L silver nitrate solution to react for 1 minute, and then rinse it with deionized water to obtain a boron-silver co-doped copper oxide composite material. The obtained composite material was structurally characterized. The results are shown in Figure 3 , as can be seen from the figure, boron nanosheets and silver nanoparticles are doped on the copper oxide nanowires.
[0052] Example 2
[0053] This embodiment provides a method for preparing a low-concentration boron-silver co-doped copper oxide composite material. The first step is the same as that of Example 1, and the different steps are as follows:
[0054] Prepare a 5mg / mL boric acid aqueous solution, drop the prepared solution on the surface of the prepared copper hydroxide nanowire template, and dry it at 60°C. Then, place the dried sample in a muffle furnace and anneal it at 500°C for 120 minutes. Take out the prepared material, put it into a 5mmol / L silver nitrate solution to react for 1 minute, take it out and rinse it with deionized water to obtain a boron-silver co-doped copper oxide composite material. The obtained composite material was tested for performance, and the results are shown in Figure 4 As can be seen from the figure, the catalytic performance when doped with boric acid at a concentration of 5 mg / L is lower than that when doped with boric acid at a concentration of 10 mg / L.
[0055] Example 3
[0056] This embodiment provides a method for preparing a high-concentration boron-silver co-doped copper oxide composite material. The first step is the same as that of Example 1, and the different steps are as follows:
[0057] Prepare a 15 mg / mL boric acid aqueous solution, drop the prepared solution on the surface of the prepared copper hydroxide nanowire template, and dry it at 60°C. Then, place the dried sample in a muffle furnace and anneal it at 500°C for 120 minutes. Take out the prepared material, put it into a 5 mmol / L silver nitrate solution to react for 1 minute, take it out and rinse it with deionized water to obtain a boron-silver co-doped copper oxide composite material. The obtained composite material was tested for performance, and the results are shown in Figure 5 It can be seen from the figure that the catalytic performance when the boric acid concentration is 15 mg / L is lower than the catalytic performance when the boric acid concentration is 10 mg / L.
[0058] Comparative Example 1 (Comparative Example without Boron Doping)
[0059] This embodiment provides a method for preparing a silver-doped copper oxide composite material. The first steps are the same as those in Example 1, and the different steps are as follows:
[0060] The prepared copper hydroxide nanowire template was placed in a muffle furnace and annealed at 500°C for 120 minutes. The prepared material was taken out and placed in a 5mmol / L silver nitrate solution for 1 minute, and then rinsed with deionized water to obtain a silver-doped copper oxide composite material. The obtained composite material was tested for performance, and the results are shown in Figure 6 As can be seen from the figure, the catalytic performance of the copper oxide composite material when only silver is doped is lower than the catalytic performance of the copper oxide composite material co-doped with boron and silver.
[0061] Comparative Example 2 (Comparative Example without Silver Doping)
[0062] This embodiment provides a method for preparing a boron-doped copper oxide composite material. The first steps are the same as those in Example 1, and the different steps are as follows:
[0063] Prepare a 10 mg / mL boric acid aqueous solution, drop the prepared solution on the surface of the prepared copper hydroxide nanowire template, and dry it at 60°C. Then, put the dried sample into a muffle furnace and anneal it at 500°C for 120 minutes. After taking out the prepared material, a boron-doped copper oxide composite material is obtained. The performance of the obtained composite material is tested, and the results are shown in Figure 7 ,It can be seen from the figure that the catalytic performance of the copper oxide composite material when only doped with boron is lower than that of the boron-silver co-doped copper oxide composite material.
[0064] Comparative Example 3 (Comparative Example without Silver and Boron Doping)
[0065] This embodiment provides a method for preparing a copper oxide composite material. The first steps are the same as those in Example 1, and the different steps are as follows:
[0066] The prepared copper hydroxide nanowire template was placed in a muffle furnace and annealed at 500°C for 120 minutes. After the prepared material was taken out, the copper oxide electrode material was obtained. The performance of the obtained material was tested, and the results are shown in Figure 8 , it can be seen from the figure that the catalytic performance of undoped copper oxide is lower than that of boron-silver co-doped copper oxide composite material.
[0067] Performance Testing
[0068] (1) The boron-silver co-doped copper oxide composite material obtained in Example 1 was subjected to CO 2 Reduction experiment, electrocatalytic CO 2 The reduction experiment used a three-electrode system and an H-type electrolytic cell was used to match it. In the electrolytic cell, an ion exchange membrane (Nafion117) was used to separate the anode chamber and the cathode chamber to prevent CO 2 The RR products are reoxidized at the anode, allowing only H + The counter electrode (CE) is made of a platinum mesh electrode, the working electrode (WE) is made of a glassy carbon electrode clip, and the reference electrode (RE) is made of a saturated Ag / AgCl electrode. 2 To accelerate dissolution and saturation, a magnetic stirrer is also installed at the bottom of the H-type electrolytic cell, and the stirrer is allowed to stir continuously in the cathode chamber. The air inlet of the cathode chamber of the H-type electrolytic cell is connected to a mass flow meter to continuously introduce CO 2 gas, allowing the electrolyte solution to CO 2 The concentration maintains a stable saturated state during the electrolysis process. Using an electrochemical workstation to provide a constant potential, CO 2 It is continuously reduced at the cathode, and its reduced gas product is introduced into the CO 2 The cathode chamber outlet is connected to the gas chromatograph inlet to achieve a dynamic flow. During the experiment, the gas chromatograph (GC) is used to maintain real-time online detection. At the same time, the outlet is connected to the GC pretreatment system, and the sample is injected through a six-way valve. Various reduction products are analyzed by gas chromatography. The experimental results are shown in Fig. 9 .from Fig. 9 It can be seen that the products of the electrocatalytic reduction of carbon dioxide by the composite material obtained in Example 1 of the present invention are H 2 ,CO,C 2 H 4 and C 2 H 6 From -0.8 to -1.2V (Vvs.RHE), the main target product of the material is C 2 H 4 Gradually increase, at -1V (Vvs.RHE) material product C 2 H 4 With C2 H 6 Reaching the highest, its total gas C 2 The Faraday efficiency FE is 50.95%, after C 2 H 4 With C 2 H 6 The Faradaic efficiency of the copper substrate gradually decreases; its overall hydrogen evolution efficiency is lower than that of other copper-based materials.
[0069] (2) The boron-silver co-doped copper oxide composite material obtained in Example 1 was subjected to CO 2 Reduction experiment, experimental results see Fig. 9 .Depend on Fig.10 It can be seen that the boron-silver co-doped copper oxide composite material has a wave potential of -1.3V (vs.Ag / AgCl) in nitrogen. 2 The potential of the copper oxide-doped boron-silver composite material in CO is higher than that in nitrogen atmosphere, which is -1V (vs.Ag / AgCl). 2 The current density in the nitrogen atmosphere is higher than that in the nitrogen atmosphere, and the difference between the two is about 20 mA cm -2 The figure shows that the prepared boron-silver co-doped copper oxide composite material has good CO reduction 2 performance.
[0070] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a boron-silver co-doped copper oxide composite material, characterized in that: The following steps are involved: providing a carbon paper; Using copper salt solution as electrolyte, the substrate material of three-dimensional porous copper film is grown on the surface of carbon paper by chronopotentiometry; The obtained base material is added into a mixed solution of an oxidant and an alkali, and allowed to stand for reaction to obtain a template with copper hydroxide nanowires loaded on the surface; Dropping a boron source solution onto the surface of the copper hydroxide nanowires in the obtained template, drying and then annealing at high temperature to obtain a copper oxide composite material doped with boron nanosheets; The copper oxide composite material doped with boron nanosheets is reacted with a silver salt solution to obtain a boron-silver co-doped copper oxide composite material.
2. The preparation method according to claim 1, characterized in that: The copper salt in the copper salt solution is selected from one or more of copper sulfate, copper chloride, copper nitrate and copper acetate; The concentration of the copper salt solution is 55-65g / L; The copper salt solution also includes an acid; The acid is selected from one or more of sulfuric acid, hydrochloric acid, and phosphoric acid; The concentration of the acid is 80-100 g / L.
3. The preparation method according to claim 1, characterized in that: The conditions of chronopotentiometry were: current 2.5-3.5 A, deposition time 15-25 s.
4. The preparation method according to claim 1, characterized in that: The concentration of the oxidant in the mixed solution is 0.045-0.055 mol / L; the concentration of the alkali in the mixed solution is 0.11-0.12 mol / L.
5. The preparation method according to claim 1, characterized in that: The oxidant is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide and potassium permanganate; the alkali is selected from sodium hydroxide and / or potassium hydroxide.
6. The preparation method according to claim 1, characterized in that: The concentration of the boron source solution is 9-11 mg / mL; The boron source in the boron source solution is selected from boric acid and / or boron oxide.
7. The preparation method according to claim 1, characterized in that: The conditions of high temperature annealing treatment are: temperature of 450-550°C and annealing time of 110-120 minutes.
8. A boron-silver co-doped copper oxide composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7; the boron-silver co-doped copper oxide composite material uses carbon paper as a carrier, and the surface of the carrier is loaded with copper oxide and CuO x , the copper oxide and CuO x Doped with boron nanosheets and silver nanoparticles.
9. The boron-silver co-doped copper oxide composite material according to claim 1, as shown in FIG11, the doping amount of the boron nanosheets is 1.00-1.40 wt%; and the loading amount of the silver nanoparticles is 30-41 wt%.
10. Use of the boron-silver co-doped copper oxide composite material according to claim 8 or 9 in electrocatalytic carbon dioxide reduction.